A Study on Reasons to use Microfinance Products in Rural District of Bengaluru (International Journal of Food and Nutritional Sciences, 2022)
Savings are a key resource for Microfinance Institutions (MFIs). They need to save enough savings to meet their obligations and become self-sufficient from grant suppliers. As a result, they need to persuade customers—in this example, the general public and micro- and small-sized businesses—to put their savings in their hands. This calls for understanding the characteristics, needs, and goals of these clients. What factors affect consumers' decisions to use and save money using an MFI's microfinance products? this raises the question of research.